Microplastic contamination in Corpus Christi Bay blue crabs, Callinectes sapidus. Issue 1 (9th January 2020) - Waddell, Elijah N.; Lascelles, Nigel; Conkle, Jeremy L.
Abstract: Microplastic pollution has been observed in marine environments around the world and has the potential to negatively impact marine organisms if ingested. Blue crabs ( Callinectes sapidus ) are susceptible to this pollution because they feed in sediment where dense plastics accumulate. Microplastic ingestion by blue crabs was assessed in Corpus Christi Bay, TX. Crab stomachs were extracted and digested using a hydrogen‐peroxide based tissue destruction method followed by material confirmation using microattenuated total reflectance Fourier transform infrared spectroscopy (μ‐FTIR). From the 39 blue crabs sampled, 28 fully synthetic fragments and fibers and 24 semisynthetic fibers were found within their stomachs. After correcting for possible contamination, 36% of collected blue crabs contained fully synthetic fragments and fibers and semisynthetic fibers with an estimate of 0.87 items per crab. This study demonstrates the need for further studies that assess the impacts of plastic ingestion on blue crabs.